2006
DOI: 10.1002/jccs.200600182
|View full text |Cite
|
Sign up to set email alerts
|

γ‐Polyglutamic Acid Produced by Bacillus Subtilis (Natto): Structural Characteristics, Chemical Properties and Biological Functionalities

Abstract: γ‐(D,L)‐Polyglutamic acid [γ‐(D,L)‐PGA, or γ‐PGA] produced by Bacillus subtilis (natto) both on laboratory and pilot scale fermenter systems has been characterized. γ‐PGA in its free acid form (H+) is insoluble in water. The salt forms of K+, Na+, NH4+, Ca2+, and Mg2+ of γ‐polyglutamates are fully soluble in water. The structural characteristics of the salts of γ‐Polyglutamates (Na+, K+, NH4+, Ca2+, and Mg2+) were determined with 1H‐ and 13C‐NMR spectroscopy and FT‐IR spectroscopy. The thermal properties were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
101
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(105 citation statements)
references
References 24 publications
3
101
0
1
Order By: Relevance
“…The thermal properties of hydrogel are affected by water content, and since hydrogel is hygroscopic, preparation upon DSC analysis can alter its water content and change its thermal property in comparison to what is usually reported in the literature [35]. In the gelatin thermogram, a broad peak at 82 °C and a relatively small peak at 225 °C correspond to its glass transition temperature, Tg, and Tm, respectively [36].…”
Section: Characterization Of Gelatin-γ-pga-based Hydrogelmentioning
confidence: 96%
“…The thermal properties of hydrogel are affected by water content, and since hydrogel is hygroscopic, preparation upon DSC analysis can alter its water content and change its thermal property in comparison to what is usually reported in the literature [35]. In the gelatin thermogram, a broad peak at 82 °C and a relatively small peak at 225 °C correspond to its glass transition temperature, Tg, and Tm, respectively [36].…”
Section: Characterization Of Gelatin-γ-pga-based Hydrogelmentioning
confidence: 96%
“…The method produces IR spectra of c-PGA with peaks corresponding to specific bonds in the compound. According to Ho et al (2006), the IR spectra of c-PGA (free acid form) and c-polyglutamate salts in KBr pellets indicate distinctive strong amide absorption at 1620-1655 cm 21 , a weaker carbonyl C5O absorption at~1394-1454 cm 21 , a strong hydroxyl OH absorption at 3400-3450 cm 21 and a characteristic strong C-N groups absorption in the range from 1085 to 1165 cm 21 . The absorption peaks between 2900 and 2800 cm 21 are characteristic of aliphatic N-H stretching, whilst those around 1600-1660 and 1390-1450 cm 21 exhibit characteristics of amide groups and C5O groups, respectively.…”
Section: Fourier Transform-ir Spectroscopymentioning
confidence: 99%
“…The PGA is an edible and biodegradable natural biopolymer composed of numerous repetitive glutamic acid units connected by γ-peptide linkage, leaving the α-carboxyl groups free for conjugation to a variety of compounds (−[−NH−CH(COOH)−(CH 2 ) 2 −CO−] n −). 20,21 It is extracellularly synthesized by Bacillus species, by either the de nova method through solid state fermentation, or by the salvage bioconversion method in submerged fermentation. 20,21 Because of its unique γ-amide linkage, multifunctionality, and flexibility to be synthesized in different ionic forms (H, Ca, Na, Mg, etc) with varying molecular weights (10,000 to 2 million Daltons), PGA finds wide application in many different fields such as food, medicine, agriculture, hygiene, cosmetics, and the environment.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 It is extracellularly synthesized by Bacillus species, by either the de nova method through solid state fermentation, or by the salvage bioconversion method in submerged fermentation. 20,21 Because of its unique γ-amide linkage, multifunctionality, and flexibility to be synthesized in different ionic forms (H, Ca, Na, Mg, etc) with varying molecular weights (10,000 to 2 million Daltons), PGA finds wide application in many different fields such as food, medicine, agriculture, hygiene, cosmetics, and the environment. 20,21 Our previous studies have demonstrated the efficiency of PGA as an adsorbent for the removal of heavy metals, organic dyes, and heterocyclic amines; [22][23][24][25] however, the application of PGA-functionalized SPIONs for removal of heavy metals remains unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation